Identifikasi Waste dengan Menggunakan Value Stream Mapping dan Upaya Perbaikan Kinerja di Gudang PT. Y - Monica Purdiani Purnomo; Indriati Bisono (Jurnal Titra, 2014)
PT. Y is one of the leading cigarette manufacturers in Indonesia. PT. Y has four warehouses i.e. DIM SKM, SPP, clove, and leaf. The company conducts continuous improvement at these warehouses, aims at lean management. Value stream mapping, one of the lean-management methods, is used to indentify waste at those warehouse. Two types of waste were found in DIM SKM warehouse, i.e. unnecessary movement and transportation waste. We proposed a new procedure to return material and a new transportation schedule. The new schedule saves one trip. Waste that is found in SPP’s raw material warehouse is waiting in which we proposed a new store location. In SPP’s production warehouse, we proposed a new schedule for goods delivery that saves two trips. To reduce unused employee creativity waste in clove warehouse we proposed a monitoring form and a new procedure. The new procedure reduces one employee. To reduce transportation waste in leaf warehouse the OTM warehouse was relocated so as the transport time save 4.5 minute/trip. These proposed improvements have been approved by the management and been implemented. The results give significant impacts.